2004
DOI: 10.1111/j.1600-079x.2004.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular second messengers involved in melatonin signal transduction in chicken splenocytes in vitro

Abstract: The pineal hormone melatonin exhibits immunomodulatory activity well documented in mammals and birds. The mechanism of melatonin action within the immune system is, however, poorly understood. In mammalian immune cells in vitro, melatonin acts mainly as an antiapoptotic, oncostatic and antiproliferative agent, and these effects are exerted via specific receptors or are related to its free radical scavenging activity. In previous studies we have found that in short-term chicken splenocyte cultures in vitro mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Our long‐term goal is to understand the physiological mechanism(s) of the action of melatonin on the chicken immune system. Previously, we demonstrated that, in chicken splenocyte cultures, melatonin stimulates proliferation, most probably through the activation of the Mel 1c receptor [21]. In the present study, we examined day/night differences in the expression of all three subtypes of membrane‐located melatonin receptors in chicken lymphoid organs and in splenocytes cultured for 30 hr.…”
Section: Discussionmentioning
confidence: 89%
“…Our long‐term goal is to understand the physiological mechanism(s) of the action of melatonin on the chicken immune system. Previously, we demonstrated that, in chicken splenocyte cultures, melatonin stimulates proliferation, most probably through the activation of the Mel 1c receptor [21]. In the present study, we examined day/night differences in the expression of all three subtypes of membrane‐located melatonin receptors in chicken lymphoid organs and in splenocytes cultured for 30 hr.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, through the dissociation of βγ subunits of Gi, melatonin activates MAP kinases as well as the Ras-MEK pathway to stimulate ERK phosphorylation (Carbajo-Pescador et al, 2011[8]; Pearson et al, 2001[42]; Witt-Enderby et al, 2003[60]). Activation of the MT2 can also result in decreases in cGMP, decreases cAMP formation and PI hydrolysis via Gαi subunit activation (Dubocovich et al, 2010[16]; Markowska et al, 2004[37]). Melatonin acted through MT1 and MT2 receptors to activate hypothalamic Akt/PKB and protein kinase B to suppress hepatic gluconeogenesis in rats (Faria et al, 2013[20]).…”
Section: Discussionmentioning
confidence: 99%
“…obs.). Other intracellular second messengers are inositol trisphosphate in splenocytes [35] and IRS‐1/PI‐3‐kinase in the hypothalamus [36], the significance of which remains to be established.…”
Section: Discussionmentioning
confidence: 99%